Real-life experience of ledipasvir and sofosbuvir single-tablet regimen among chronic hepatitis C patients in Turkey - Yamazhan, Tansu; Turan, İlker and Ersöz, Galip and Günşar, Fulya and Pullukçu, Hüsnü and Danış, Nilay and Ünal, Nalan G. and Vardar, Rukiye and Oruç, Nevin and Tekin, Fatih and et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Ledipasvir (LDV) and sofosbuvir (SOF) as single-tablet regimen (STR) has been approved for treatment of chronic HCV infection (CHC) for treatment-naïve or experienced cirrhotic or non-cirrhotic patients. Our aim was to analyse the effectiveness and safety of 12-24 weeks treatment of LDV/SOF (90mg/400 mg)±ribavirin in a real-life setting in Turkey. Materials and Methods: Between May-Dec 2016, 104 treatment-naïve or experienced adult patients with CHC and with or without cirrhosis (including decompensated cirrhosis) were included in this observational study. Patients were administered LDV/SOF STR± ribavirin once daily for 12 -24 weeks. SVR12 rates and effects of the baseline characteristics on SVR12 rates were assessed. Results: Out of 104 enrolled patients (61.5% female, mean age 62.0 years); 60.6% were cirrhotic, 76.0% previously used peg-IFN, 94.2% had GT1. At the end of the treatment, 77.8% (77/99, no data for 21 patients) had undetectable HCV-RNA and 98.9% (94/95) had SVR12. In the baseline characteristics subgroups, the SVR12 rates varied between 94.4% and 100%, and none of the baseline characteristics had a significant effect on the SVR12 rates. During the study, 6 (5.8%) patients died and none of the deaths was suspected to be related to the LDV/SOF. No treatment-emergent adverse event was reported. Conclusion: In conclusion, LDV/SOF±ribavirin yielded very high SVR12 rates, without any safety or tolerability concern in Turkey. The effectiveness of the LDV/SOF treatment was not affected by the patient demographics or medical characteristics such as fibrosis level, cirrhosis status, previous treatment status, HCV-RNA level or HCV genotype.